Design and Challenges of Sonodynamic Therapy System for Cancer Theranostics: From Equipment to Sensitizers - Gong, Zhuoran; Dai, Zhifei (Advanced science, 2021)
As a novel noninvasive therapeutic modality combining low‐intensity ultrasound and sonosensitizers, sonodynamic therapy (SDT) is promising for clinical translation due to its high tissue‐penetrating capability to treat deeper lesions intractable by photodynamic therapy (PDT), which suffers from the major limitation of low tissue penetration depth of light. The effectiveness and feasibility of SDT are regarded to rely on not only the development of stable and flexible SDT apparatus, but also the screening of sonosensitizers with good specificity and safety. To give an outlook of the development of SDT equipment, the key technologies are discussed according to five aspects including ultrasonic dose settings, sonosensitizer screening, tumor positioning, temperature monitoring, and reactive oxygen species (ROS) detection. In addition, some state‐of‐the‐art SDT multifunctional equipment integrating diagnosis and treatment for accurate SDT are introduced. Further, an overview of the development of sonosensitizers is provided from small molecular sensitizers to nano/microenhanced sensitizers. Several types of nanomaterial‐augmented SDT are in discussion, including porphyrin‐based nanomaterials, porphyrin‐like nanomaterials, inorganic nanomaterials, and organic–inorganic hybrid nanomaterials with different strategies to improve SDT therapeutic efficacy. There is no doubt that the rapid development and clinical translation of sonodynamic therapy will be promoted by advanced equipment, smart nanomaterial‐based sonosensitizer, and multidisciplinary collaboration. As a novel noninvasive cancer therapeutic modality, sonodynamic therapy (SDT) is promising to clinical translation, in spite of several problems in equipment and sensitizer. The recent development in SDT in terms of living monitoring and high accuracy treatment system is highlighted and an overview is provided for advanced sonosensitizer design. The challenge in future clinical use is also discussed.